2022
DOI: 10.3390/foods11030333
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Limosilactobacillus fermentum UCO-979C with Anti-Helicobacter pylori and Immunomodulatory Activities in Various Ice Cream Bases

Abstract: Limosilactobacillus fermentum UCO-979C is a probiotic strain possessing anti-Helicobacter pylori and immunomodulatory activity. The aim of this work was to examine if this strain maintains its probiotic properties and its viability when added to dairy-based ice creams (cookies and cream, Greek yogurt, and chocolate with brownie) or to fruit-based ice creams (pineapple and raspberry) stored at −18 °C for 90 days. The probiotic anti-H. pylori activity using the well diffusion test, its immunomodulatory activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Further studies by Boyanova et al [ 62 ] revealed that the DIZ of some Lactobacillus strains were higher, from 13 to 16 mm, while Chen et al [ 63 ] found that L. rhamnosus and L. acidophilus exhibited an inhibitory effect against H. pylori reference strain 26695 demonstrated by a DIZs of 12.3 and 11.3 mm, respectively [ 62 , 63 ]. However, Paucar-Carrión et al [ 61 ], when analyzing the anti- H. pylori activity of L. fermentum, concluded that the activity was mild with DIZ between 1 mm and 2 mm [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further studies by Boyanova et al [ 62 ] revealed that the DIZ of some Lactobacillus strains were higher, from 13 to 16 mm, while Chen et al [ 63 ] found that L. rhamnosus and L. acidophilus exhibited an inhibitory effect against H. pylori reference strain 26695 demonstrated by a DIZs of 12.3 and 11.3 mm, respectively [ 62 , 63 ]. However, Paucar-Carrión et al [ 61 ], when analyzing the anti- H. pylori activity of L. fermentum, concluded that the activity was mild with DIZ between 1 mm and 2 mm [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…The biomass obtained was resuspended in 20% skim milk, frozen at −45 °C, lyophilized using a model BK-FD10PT freeze dryer (Biobase, Shandong, China) and kept at 4 °C in the dark until used. Counts indicated the presence of 10 10 CFU g −1 of lyophilized powder [ 29 ]. Regarding the preparation of the gelatins, the probiotic strain L. fermentum UCO-979C, >10 7 colony-forming units (CFUs) mL −1 , was incorporated into three-layer gelatin (100 g serving) ( Figure 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…H. pylori e inmunomoduladora de esta cepa, además de la viabilidad, cuando ella se incorporaba en helados lácteos o en helados de frutas con base acuosa, en éstos la cepa mantuvo una fuerte actividad anti-H. pylori de la cepa probiótica aislada desde los helados de bases lácteas y una actividad leve para aquellas cepas que fueron aisladas desde helados de frutas con base acuosa, ya que las cepas aisladas desde helados de base láctea produjo en mayor cantidad citoquinas proinflamatorias TGF-β1; además, incorporar la cepa al producto no modificó sus propiedades fisicoquímicas [35]. En un ensayo aleatorizado doble ciego controlado por un placebo realizado por Parra C. & col [36] administraron gelatina suplementada con L. fermentum UCO-979C una vez al día, cinco días a la semana, durante 12 semanas consecutivas a los distintos individuos involucrados en el estudio, demostraron que se evitó la infección por H. pylori, con una eficacia del 92,6% en individuos no infectados.…”
Section: Capacidad Inmunomoduladora De L Fermentum Uco-979cunclassified